Bone and joint infections from microbiology to diagnostics and treatment - Zimmerli, Werner, 1948- (John Wiley & Sons Inc., 2015)
Covering the basic microbiology and clinical aspects of bone and joint infection, this book will be a valuable resource both for researchers in the lab and for physicians and surgeons seeking a comprehensive reference on osteomyelitis and septic arthritis.